Comparative Analysis of Public Cloud Security Based Schemes and Cryptographic Algorithms - G Nagarajan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud computing has been established as the next renewable technology in the IT world. While numerous cloud protection assessments are now prevalent, there is still some disparity between the accurate mapping of problems and their related solutions. Cloud data storage is fast, but the information we store must be safe, and the information stored in the cloud-managed the cloud service providers or the cloud caregiver. The data owner is worried about the integrity and trustworthiness of data stored in the cloud. In this article, a detailed comparative examination of different schemes and “cryptography algorithms” used to protect information over the public cloud will be carried out and provided a clear review of various methods and their limitations in tabular format.